Understanding the everyday use of images on the Web - Chew, Boon; Rode, Jennifer; Sellen, Abigail (Proceedings of NordiCHI 2010, 2010)
This paper presents a qualitative study of domestic Web-based image use, and specifically asks why users access images online. This work is not limited to image search per se, but instead aims to understand holistically the circumstances in which images are accessed through Web-based tools. As such, we move beyond the existing information seeking literature, and instead provide contextual examples of image use as well as an analysis of both how and why images are used. The paper concludes with design recommendations that take into account this wider range of activities.